2016
DOI: 10.14238/sp10.3.2008.151-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalensi dan Faktor Risiko Enuresis pada A nak Taman Kanak-Kanak di Kotamadya Denpasar

Abstract: Enuresis diurnal adalah enuresis yang terjadi saat siang ha ri sedangkan enuresis nokturnal adalah enuresis yang ter jadi saat anak tertidur di malam hari. Menurut awal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
10
3
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 7 publications
(15 reference statements)
6
10
3
7
Order By: Relevance
“…This is contrary to previous studies that reported only a small proportion had a family history of enuresis [14], [16], [17]. Family enuresis history is a genetic factor of enuresis [14] the role of genes located on chromosome 12 q (gene ENUR-2) in the occurrence of enuresis. In addition, genes carrying these enuresis properties are also found on chromosome 13 q (ENUR-1) and 22 (ENUR-3) [3].…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…This is contrary to previous studies that reported only a small proportion had a family history of enuresis [14], [16], [17]. Family enuresis history is a genetic factor of enuresis [14] the role of genes located on chromosome 12 q (gene ENUR-2) in the occurrence of enuresis. In addition, genes carrying these enuresis properties are also found on chromosome 13 q (ENUR-1) and 22 (ENUR-3) [3].…”
Section: Discussioncontrasting
confidence: 95%
“…The study also reported that children generally do not experience constipation. In line with the results of Windiani study in Bali which stated that only 7.8% of children constipated [14], Sureshkumar in Australia with only 5.7% of enuresis [21], Kurniawan in Pekalongan, 17.1 % of children have constipation [22]. However, the study in Canada reported more than half (57.54%) of children had constipation [23].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…36 The prevalence of enuresis in Indonesia from several studies was about 10.9%. 37 In our study, 18 of 110 children had enuresis, based on the IACAPAP Questionnaire. 1 The prevalence of enuresis was 16.4%, with 10 (9.1%) males and 8 (7.3%) females.…”
Section: Discussionmentioning
confidence: 74%